Very High Efficiency Porous Silica Layer Open-Tubular Capillary Columns Produced via in-Column Sol-Gel Processing - Hara, Takeshi; Futagami, Shunta; Eeltink, Sebastiaan; De Malsche, Wim; Baron, Gino V; Desmet, Gert (Analytical chemistry (Washington), 2016)
It is demonstrated that 5 μm i.d. capillaries can be coated with mesoporous silica layers up to 550 nm thickness. All the columns produced using in-column sol-gel synthesis with tetramethoxysilane provide plate height curves that closely follow the Golay-Aris theory. In 60 cm long columns, efficiencies as high as N = 150 000 and N = 120 000 were obtained, respectively, for a 300 and 550 nm thick porous layer. An excellent retention and plate height reproducibility was obtained when the recipes were subsequently applied to produce very long (1.9 and 2.5 m) capillaries. These columns produced efficiencies up to N = 600 000 plates for a retained and around N = 1 000 000 plates for an unretained component. Given the good reproducibility on the long capillaries, and considering that mesoporous silica is still the preferred support for LC, it is believed the present study could spur a renewed interest in open-tubular LC.